The Perception Of Local Frontliners On Local-Level Ecotourism Institutional Arrangement For Resource Protection In Kuala Tahan, Taman Negara Pahang - Yip, Hin Wai (2005)
A survey was administered using questionnaires to obtain the local frontliners' opinions on ecotourism institutional arrangement for resource protection in Kuala Tahan, Taman Negara Pahang. The survey was conducted to 103 respondents comprising the personnel of the Taman Negara management and local entrepreneurs, including guides, boat operators, floating restaurants owners and chalet operators and resort's staffs. The questionnaires cover the frontliners' perception regarding tourism impacts on natural resources, local-level institutional arrangement, and the socio-demographic backgrounds. Descriptive, x2 test, factor analysis, and regression analysis were applied to analyse the data. The results of the study showed that most of the respondent perceived the impacts of ecotourism to be not serious. Further analysis showed that there were significant differences in perception among the various income groups in relation to she impacts on the resources. The results showed that there were significant differences in terms of their perceptions on loss of ground cover plants, wildlife displacement. number of wildlife reduced. loss of Park's resources (for example, taking of plants and rocks for souvenirs), littering, and water pollution. Here, the frontliners who received higher income (above RM2000) were more concerned about the resource condition. In addition, there were significant differences between frontliners of park management and non-park management on their perception toward impacts on wildlife. The results of factor analysis indicated that the local-level institutional arrangement factors in Taman Negara as perceived by local frontliners were joint management operation (eigenvalue of 4.399), sharing of technical skills (2.528), adoption of best practices (2.088) and intellectual forum (1.062), which should be recognised by both parties. Based on the eigenvalues, a conceptual framework for local-level institutional arrangement was developed and discussed to show how different frontliners could involve in the arrangement. The results of regression analysis showed that socio-demographical backgrounds of frontliners did not influent the agreement upon this institutional arrangement with the exception of age. Older frontliners had better understanding upon the benefits of this type of involvement or participation and able to accept this arrangement that eventually helps to protect the park's resources. In other words, through years of personal learning and experience in ecotourism, it is expected that the frontliners are willing to accept this initiative in which they will gain direct benefits through the participation of ecotourism activities.